Blockchain-enabled traceability and certification for frozen food supply chains: A conceptual design - Uyar, Havva; Papanikolaou, Athanasios; Kapassa, Evgenia; Touloupos, Marios; Rizou, Stamatia (My University, 2025)
Ensuring traceability, compliance certification and cold chain integrity in frozen food supply chains remains a persistent challenge, exacerbated by fragmented monitoring systems, manual audits and vulnerability to data manipulation. This study presents a conceptual design for a blockchain-enabled compliance architecture that addresses these challenges by integrating real-time Internet of Things (IoT) data acquisition, permissioned blockchain-based data storage and smart contract-driven compliance automation. Following a Design Science Research (DSR) methodology, the research focuses on the initial phases (problem identification, objective specification and artefact conceptualization) providing a structured foundation for future demonstration and evaluation. The proposed design is structured across three interdependent layers: (1) a Data Acquisition Layer that ensures continuous and secure sensor-based monitoring; (2) a Data Storage Layer that leverages blockchain for immutable recording and transparent auditability; and (3) an Application Layer that integrates smart contracts for automated compliance enforcement and user interfaces for stakeholder interaction. By translating regulatory compliance requirements into a modular, blockchain-based design, this work contributes to the theoretical grounding of decentralized regulatory infrastructures in agri-food systems. The proposed architecture embodies design principles that may inform similar traceability systems across other regulated supply chains. Although empirical validation is forthcoming, the conceptualization serves as a scaffold for future DSR iterations and contributes to design knowledge in the domain of digital compliance architectures.
Keywords: Blockchain; Cold chain compliance; Ethereum; Smart contract; Solidity